Constituent Factors of Intelligence-Based Academic Governance: Developing a Qualitative Framework (Case Study: Comprehensive Universities of Tehran) - Nourozi, Sima; Ahmadi, Fakhrodin; Shafizadeh, Hamid (Assessment and Practice in Educational Sciences, 2025)
The present study was conducted with the aim of identifying the constituent factors of intelligence-based academic governance in the comprehensive universities of Tehran and developing a qualitative framework for it. From the perspective of purpose, the study is applied; in terms of data, it is qualitative based on a systematic grounded theory approach; and in terms of implementation, it is exploratory with an inductive orientation. The statistical population consisted of university faculty members in the fields of governance and management, considering scientific criteria (research experience). Using a purposive and snowball sampling method, 14 interviews were conducted until theoretical saturation was reached. For data collection, both library methods (document analysis) and field methods (semi-structured interviews) were employed. To ensure the validity of the findings, triangulation was applied, including reliability, credibility, confirmability, and transferability, which indicated that the data possessed the required validity. Data were analyzed using theoretical coding in three stages: open coding, axial coding, and selective coding (based on the systematic grounded theory method of Strauss and Corbin). The results revealed that the constituent factors of intelligence-based academic governance in universities include 22 components and 121 indicators within the six dimensions of the paradigm model, as follows: Central phenomenon of the model with 2 components (self-management and knowledge governance) and 13 indicators. Causal factors of the model with 4 components (rule of law, national and international developments, institutional independence, competence of governing bodies) and 21 indicators. Contextual factors of the model with 4 components (intelligent university communications, intelligent administrative management, intelligent scientific services, financial resource management) and 24 indicators. Intervening factors of the model with 3 components (organizational culture, structural factors, technological factors) and 16 indicators. Strategies of the model with 5 components (quality assessment and improvement, scientific independence, stakeholder participation in decision-making, redesign of structures and processes, intelligent qualitative academic programs) and 25 indicators. Consequences of the model with 4 components (enhancing the university’s brand, educational innovation, improving the quality of teaching and research, and training efficient and entrepreneurial human resources) and 22 indicators. Based on the identified factors, a qualitative framework was developed and validated by experts. Utilizing the findings of scientific research on intelligence-based academic governance can help universities leverage the scientific and executive capacities of faculty members and act in ways that not only enhance and develop the university itself but also make significant contributions to national development.